(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2022)
The essay discusses a continuous science teachers’ training, which occurred in a capixaba coastal plain in order to evaluate their pedagogical potentialities, in order to make the participants capable of conducing field classes for favoring the development of educational actions that allow a critical reading of the context in which they are inserted. Took part in the formation 26 students of the IFES Graduate Program, most of them teachers from public schools. It is a qualitative research activity, which used participant observation techniques and the registration of photographs and field diary for data collecting. The results showed that they have never taken part in a field class before, although this activity confers social meaning to the non formal educational settings.